Preference ranking test for different icon design formats for smart living room and bathroom functions. (November 2019) - Chi, Chia-Fen; Dewi, Ratna Sari; Samali, Priska; Hsieh, Dong-Yu
Abstract: The current study illustrates the icon design process for 20 functions for a smart living room and smart bathroom of a commercial smart building control system. For each function name, seven icon formats ( image - related, concept - related, semi-abstract, arbitrary, word, abbreviation, and combined) were developed by 30 graduate students and compared with a preference ranking test by another 13 executive MBA students. The results indicated that the combined, image-related, concept-related, semi-abstract, word, and abbreviation each had nine, four, three, two, one and one function names ranked as the most preferred format, respectively. Since all the design formats except the arbitrary format were ranked as the most preferred at least once, it is worthwhile to generate seven icon formats for a given function and chose the most preferred based on the ranking test result. The participatory design and ranking test evaluation approach can be applied for the design and evaluation of visual icons in other application contexts. Highlights: Seven icon formts for 15 functions for smart living room and 5 functions for smart bath room were developed and compared using a preference ranking test. Nine out of 20 functions had the combined icon format ranked as the most preferred. It is worthwhile to generate seven icon formats for a given function and chose the most preferred based on the ranking test result.